2008
DOI: 10.1590/s0034-89102008005000042
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and related risk behaviors in a community of recyclable waste collectors of Santos, Brazil

Abstract: HIV infection and related risk behaviors in a community of recyclable waste collectors of Santos, BrazilInfecção por HIV e comportamentos de risco relacionados em coletores de lixo de Santos, Brasil ABSTRACT OBJECTIVE: To estimate the seroprevalence of HIV, hepatitis B and C and syphilis and to describe risk behaviors associated to their transmission among recyclable waste collectors. METHODS:A seroepidemiological survey was carried out in the city of Santos, Southeastern Brazil, in 2005. A total of 315 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 2 publications
4
18
2
13
Order By: Relevance
“…Compared with the prevalence in other Brazilian populations, the prevalence determined in this study was within the confi dence interval range recorded for patients attending an STD clinic (13%; 95% CI: 10.0-16.5) 20 , non-injection drug users (14%; 95% CI: 11.7-16.5) 21 and individuals reporting to an HIV testing and counseling center (14.6%; 95% CI: 11.2-18.0) 22 . Nevertheless, relative to other reported data on recyclable waste collectors, the prevalence found in the present study was lower than that observed in Santos, Brazil (34.4%; 95% CI: 28.5-40.2) 14,15 . This difference may refl ect differences in the rates of risky behaviors between the studied groups in Goiânia and Santos.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Compared with the prevalence in other Brazilian populations, the prevalence determined in this study was within the confi dence interval range recorded for patients attending an STD clinic (13%; 95% CI: 10.0-16.5) 20 , non-injection drug users (14%; 95% CI: 11.7-16.5) 21 and individuals reporting to an HIV testing and counseling center (14.6%; 95% CI: 11.2-18.0) 22 . Nevertheless, relative to other reported data on recyclable waste collectors, the prevalence found in the present study was lower than that observed in Santos, Brazil (34.4%; 95% CI: 28.5-40.2) 14,15 . This difference may refl ect differences in the rates of risky behaviors between the studied groups in Goiânia and Santos.…”
Section: Discussioncontrasting
confidence: 97%
“…These fi ndings support previously reported data, reinforcing the importance of establishing educational and health policies that address the safety of this population 6,7,9,11,15 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Os catadores, de modo geral, possuem uma residência; uma porcentagem muito pequena mora nas ruas ou reside em depósitos de materiais recicláveis (9) .…”
unclassified